ANALISIS PEMASANGAN TRANSFORMATOR SISIP UNTUK MENGATASI TRAFO PSG.039 OVERLOAD PENYULANG MG.07 DI ULP MATANG GELUMPANG DUA - Nawawi, Ikram; Sutejo, Eddy; Satria, Beni (Power Elektronik : Jurnal Orang Elektro, 2024)
The MG.07 Substation in Matang Gelumpang Dua is located in the PT. PLN (Persero) Customer Service Unit Matang Gelumpang Dua Area Bireun, supplied by the Bireun Main Substation with a feeder capacity of 280 A. The MG.07 feeder supplies transformer PSG.039, loaded at 103.4% of its 250 kVA capacity. The standard load for a transformer is 80% of its capacity. The solution to address this issue is to install an insert transformer to distribute the load from PSG.039. According to data from PT. PLN (Persero) Area Bireun in 2023, the annual increase in electricity usage in Matang Gelumpang Dua Bireun is 8.3%. Therefore, using a 250 kVA insert transformer with an initial loading percentage of 26.8%, it will be able to accommodate the increase in electricity usage for the next five years, with a total loading percentage after five years of 68.3%.